Clinical and imaging characteristics of familial gigantiform cementoma. A review of the literature - Rodríguez-Cuentas, Grizel Karem (2021)
Familial gigantiform cementoma (FGC) is a rare benign fibro-cementum lesion, which follows an autosomal dominant inheritance pattern and presents during childhood. It is limited to the bones of the face, with a predilection for the jaw, is fast growing and painless and expands considerably over time. It is considered among the seven disorders that affect the physiognomy of the craniofacial skeleton. Radiographically, FGC occurs in three stages of maturation similar to bone dysplasia, being radiolucent, mixed and radiopaque and is described as a mixed lobular well delimited mass, which can occur in both maxillae, causing expansion of the buccal and palatal / lingual bone cortices. displacement and retention of teeth. The aim of this study was to perform a review of the literature to identify the clinical, radiographic and histopathological characteristics of FGC in the jaws and describe the imaging tools that are useful for the diagnosis and follow-up of this lesion.